Psychological Stress in Childhood and Myopia Development. - Katz, Louise; Berlin, Kristoffer S. (Optometry & Visual Performance, 2014)
Background: Myopia is a common human vision problem and is increasing in prevalence, yet its etiology remains unclear. A role of psychological stress in the etiology of various ocular disturbances has been suggested, but virtually no research has explored a possible link between psychological stress and myopia development. Methods: In this extension of a recent study, participants (n = 457) who were predominantly undergraduate students completed an anonymous survey assessing both their adult evaluation and retrospective childhood evaluation of their childhood stress. Results: Myopic participants had a significantly higher score on the Stress-Fear-Abuse scale in a factor analysis than did emmetropic participants. Exploratory analyses suggested that myopes in their childhood had lower self-esteem, were more lonely, experienced more criticism about physical aspects of themselves, had higher weight, sat closer to the television, and may have experienced more fear and more very stressful events or situations. Conclusions: Our data suggest that, based on adult evaluations, myopic children have more childhood stress, and based on retrospective childhood evaluations, there is no difference in experience of certain specific childhood stressors. Our data suggest, therefore, that myopic children may have perceptual problems related to recognition and interpretation of stressful situations in their lives. Our findings point to possible unexplored risk factors for myopia and suggest complex interrelationships between psychological stress, childhood emotions, and myopia development in children.